Identity in The House on Mango Street, Beloved, and in The Woman Warrior: Names and Naming - Surányi, Ágnes (FOCUS: Papers in English Literary and Cultural Studies, 2024)
It becomes apparent at first reading that in any of the three works to be examined, naming (i.e. the naming of characters by the authors, the characters’ addressing themselves and each other individually or in community, the names identifying them when they are spoken to by members of the white majority) has much relevance in the shaping of identity. In ethnic literatures, where personal and communal identity as well as identity in the larger context of society are a matter of life and death, names do matter for both writer and reader, and deserve attention.